(untitled) (World Bulletin of Management and Law, 2025)
The article aims to analyze the state bodies and institutions involved in the staffing personnel for the state civil service. As a result of the research, these institutions were divided into 2 large groups: general authorized entities and special authorized entities. The study emphasizes the legal and organizational frameworks that regulate the selection and appointment of civil servants. It also explores the role of institutional coordination in ensuring merit-based recruitment. Comparative analysis with foreign practices highlights strengths and gaps in the current system. The article further discusses the influence of administrative reforms on human resource management in the public sector. Special attention is paid to the transparency and efficiency of recruitment mechanisms within the civil service system